Measuring public opinion and acceptability of prevention policies: an integrative review and narrative synthesis of methods - Eloise Howse; Katherine Cullerton; Anne Grunseit; Erika Bohn-Goldbaum; Adrian Bauman; Becky Freeman (BMC, 2022)
Abstract Acceptability of and public support for prevention are an important part of facilitating policy implementation. This review aims to identify, summarize and synthesize the methods and study designs used to measure and understand public opinion, community attitudes and acceptability of strategies to prevent chronic noncommunicable disease (NCDs) in order to allow for examination of imbalances in methodological approaches and gaps in content areas. We searched four scientific databases (CINAHL, Embase, Ovid/MEDLINE and Scopus) for peer-reviewed, English-language studies published between January 2011 and March 2020 in high-income, democratic countries across North America, Europe and the Asia-Pacific region. Studies were included if they focused on opinions, attitudes and acceptability of primary prevention strategies and interventions addressing the key NCD risk factors of alcohol use, unhealthy diet, overweight/obesity, tobacco use and smoking, and physical inactivity. A total of 293 studies were included. Two thirds of studies (n = 194, 66%) used quantitative methods such as cross-sectional studies involving surveys of representative (n = 129, 44%) or convenience (n = 42, 14%) samples. A smaller number of studies used qualitative methods (n = 60, 20%) such as focus groups (n = 21, 7%) and interviews (n = 21, 7%). Thirty-nine studies (13%) used mixed methods such as content analysis of news media (n = 17, 6%). Tobacco control remains the dominant topic of public opinion literature about prevention (n = 124, 42%). Few studies looked solely at physical inactivity (n = 17, 6%). The results of this review suggest that public opinion and acceptability of prevention in the peer-reviewed literature is investigated primarily through cross-sectional surveys. Qualitative and mixed methods may provide more nuanced insights which can be used to facilitate policy implementation of more upstream strategies and policies to prevent NCDs.